2018
DOI: 10.1007/s40092-018-0267-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing an appropriate staff mix for anticoagulation clinics: functional job analysis approach

Abstract: Anticoagulation clinics (ACCs) are specialty clinics that manage patients with blood clotting problems. Since labor costs usually account for a substantial portion of a healthcare organization's budget, optimizing the number and types of staff required was often the focus, especially for ACCs, where labor-intensive staff-patient interactions occur. A significant portion of tasks performed by clinical pharmacists might be completed by clinical pharmacist technicians, which are lessexpensive resources. While nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The first result of this study proved that there is a positive effect of job analysis on job performance which corresponds to the pay model as well as with many of the studies previously discussed above ( Atteya, 2012 ; Hailemariam et al., 2019 ; Milkovich et al., 2013 ; Mira et al., 2019 ; Nyasha et al., 2013 ; Okumbe, 1999 ). Moreover, this study found a positive effect of job analysis on procedural justice, which is consistent with equity theory and many of the studies that were previously discussed ( Pan et al., 2018 ; Swalhi et al., 2017 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The first result of this study proved that there is a positive effect of job analysis on job performance which corresponds to the pay model as well as with many of the studies previously discussed above ( Atteya, 2012 ; Hailemariam et al., 2019 ; Milkovich et al., 2013 ; Mira et al., 2019 ; Nyasha et al., 2013 ; Okumbe, 1999 ). Moreover, this study found a positive effect of job analysis on procedural justice, which is consistent with equity theory and many of the studies that were previously discussed ( Pan et al., 2018 ; Swalhi et al., 2017 ).…”
Section: Discussionsupporting
confidence: 83%
“…Through job analysis, organization can predict employees’ performance; and how to reward each of them through their performance. In addition, employees know the performance that organization expects from them, and how they will be compensated for that ( Hailemariam et al., 2019 ). Job analysis data can distinguish the knowledge, skills, abilities, and expertise which are necessary for effective and high level of performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The job analysis helps the human resource manager quantify the duties of the job and the appropriate salary for the hired employees. Through the job analysis, the organization knows what to expect from the employees and how to reward employees who demonstrate good performance; and in return, the employees know what the organization expects from them and the type of compensation and reward they receive (Hailemariam et al, 2019). The recruitment & selection process is another critical process that influences the employees' performance and productivity.…”
Section: Adams' Equity Theorymentioning
confidence: 99%
“…Under this examination, it is considered as free factor that impact the performance of the workers, assuming employees are remunerated on their obligations, they are more useful. By expected set of responsibilities, the organization knows about what to assume from the specialists and how to remunerated laborers who decide great performance; and consequently, the workers know what the organization accepts from them and the assortment of pay and prize they get (Hailemariam et al, 2019).…”
Section: Reward and Compensationmentioning
confidence: 99%